Development of fluid applicator valve and optimization of production process (Research, Society and Development, 2022)
This work presents as a theme the development of a fluid applicator valve and optimization of the production process. The objective of this study is to develop an improvement and optimize a process within a multinational industry, from a problem identified and reported by a customer through the Customer Satisfaction platform. At the stage of developing the action plan the quantitative research methodology was used, since several numbers were collected and statistical techniques were applied, such as indicators of production, quality, strategic performance and competitiveness. The qualitative methodology was used in the benchmarking with the employees of the company and also in the receipt of the customer's complaint. It was concluded from the hypotheses raised by this work that to develop the improvement in the oil applicator decreased the contamination of the product. Other validated hypotheses are that developing an improvement in the oil applicator reduced the level of drip and implanting the new applicator valve prevented further customer complaints about the problem.